Legislación de emergencia y reforma laboral en España (2011-2012) - Sempere, Antonio (2012)
Emergency legislation and labor reform in Spain(2011-2012) Spanish Labor Law is going through a phase of continuous and disordered reforms, most of them made through approved rules by the Government invoking raisons of urgency. Here are explained six recent andrelevant Royal Decrees-Laws approved between 2010 and 2012